E-221 Most ruptured aneurysms are small with low rupture risk scores. (23rd July 2022) - Webb, M; Fischer, V; Farrell, R; Towne, J; Birnbaum, L; Rodriguez, P; Mascitelli, J
Abstract : Background: Understanding the rupture risk of unruptured intracranial aneurysms has important clinical implications given the morbidity and mortality associated with subarachnoid hemorrhage (SAH). The ISUIA, UCAS, and PHASES studies provide rupture risk calculations. Objective: We apply the risk calculations to a series ruptured intracranial aneurysms to assess the rupture risk for each aneurysm (had they been discovered in the unruptured state). Methods: This is a retrospective study of 246 patients with SAH from a ruptured saccular aneurysm. The ISUIA, UCAS, and PHASES calculators were applied to each patient/aneurysm to demonstrate a theoretical annual risk of rupture dichotomized by aneurysm location. Results: The average diameter of the aneurysms was 5.5±3.1 millimeters. Three quarters (75%) of the aneurysms measured less than 7 mm and 48.8% were less than 5 mm. The anterior communicating artery (Acomm) was the most common location of rupture (24.7%). Posterior communicating artery aneurysms (Pcomm) were the third most common at 16.2%. The average ISUIA 1-year rupture risk was 0.46±.008%. The average UCAS 1-year rupture risk was 0.93%±.01. The annual PHASES rupture risk was 0.32±.004%. The highest risk locations were the vertebral artery (up to 10.3% per year) and superior cerebellar artery (up to 2.7% per year). On average, Acomm aneurysms had 1 year risk no higher than 1.1% and Pcomm aneurysms no higher than 1.2% per year. Conclusion: The majority of ruptured aneurysms are small (< 7mm) and the average annual rupture risk (had they been discovered in the unruptured state) is low (< 1% per year). Disclosures: M. Webb: None. V. Fischer: None. R. Farrell: None. J. Towne: None. L. Birnbaum: None. P. Rodriguez: None. J. Mascitelli: 2; C; Stryker.